Pengembangan Media Diorama Augmented Reality Materi Alat Indra dengan Model Discovery Learning untuk Meningkatkan Kemampuan Kognitif Siswa Kelas IV Sekolah Dasar - Wiwin Natalia; Endang Widi Winarni; Osa Juarsa (UNIB Press, 2026)
This study aims to develop discovery learning-based augmented reality diorama media to improve students' cognitive abilities. The study was conducted at SDN 57 Bengkulu City in grade IV. This study is a development research (Research and Development) with the model The research model in development is the ADDIE model. The object of the study is discovery learning-based augmented reality diorama media to improve students' cognitive abilities. The instruments used were a feasibility test questionnaire and student response questionnaire and teacher interview guidelines. The feasibility test was carried out by 6 validators, namely 2 material experts, 2 language experts and 2 graphic experts. The user response test was carried out on 25 fourth-grade students and 1 class teacher in the trial class. The results of the teaching media feasibility test by the validator were reviewed from the material, language, and graphic aspects, the material feasibility was obtained 70.8% (feasible criteria), the language feasibility results 75% (feasible criteria) and the graphic feasibility results 79.1% (feasible criteria). The results of the field test of the teaching media, conducted by conducting pre- and post-tests, showed an average pre-test score of 53.2, increasing to 82 in the post-test. Meanwhile, the gain test showed a result of 0.61, which is categorized as moderate. In other words, the teaching media used provides benefits and is effective for use as a learning medium in improving students' cognitive abilities.